2018
DOI: 10.1016/j.trci.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A novel two‐day intervention reduces stress in caregivers of persons with dementia

Abstract: IntroductionCaregivers of individuals with dementia are at heightened risk for stress-related mental and physical illnesses, and this problem is growing. There is a critical need to develop effective interventions for caregivers. This study tested whether a 2-day intervention improved psychological health in caregivers of individuals with dementia.MethodsFamily caregivers (N = 104) were randomly assigned to a 2-day intervention or wait-list control group. The intervention uses techniques aimed at fostering sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Our analyses did not show a statistically significant difference in the level of subjective caregiver burden between those who applied vs. did not apply the communication methods (reminiscence and validation according to Naomi Feil). As the validation has not yet been investigated in relation to the caregiver burden of PLwD as an independent intervention, the findings from multi-component psychosocial interventions ( 54 ) are available only, who investigated the caregiver burden and stress among 104 informal caregivers. While, the assumption about significantly decreased caregiver burden 1, 3, and 6 months post-intervention was not confirmed, the perceived stress was significantly reduced only after 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses did not show a statistically significant difference in the level of subjective caregiver burden between those who applied vs. did not apply the communication methods (reminiscence and validation according to Naomi Feil). As the validation has not yet been investigated in relation to the caregiver burden of PLwD as an independent intervention, the findings from multi-component psychosocial interventions ( 54 ) are available only, who investigated the caregiver burden and stress among 104 informal caregivers. While, the assumption about significantly decreased caregiver burden 1, 3, and 6 months post-intervention was not confirmed, the perceived stress was significantly reduced only after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…While, the assumption about significantly decreased caregiver burden 1, 3, and 6 months post-intervention was not confirmed, the perceived stress was significantly reduced only after 6 months. Almost all respondents found validation particularly helpful in managing the behavioral challenges associated with dementia ( 54 ). These findings support the original hypothesis by Feil (1992 in Canon ( 55 ), p. 12) who stated that the validation “reduces stress and frustration in caregivers in social care facilities by improving interpersonal communication and developing a more meaningful relationship with the person with dementia.” Other three studies investigated the effect of multi-component and emotion-oriented interventions, including validation, and were devoted to increasing satisfaction and reducing stress symptoms in professional workers in health and social services ( 33 , 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two hundred twenty-four RCTs representing more than 50 000 patients, caregivers, or both and 3 cohort studies with more than 190 000 patients were identified that addressed the treatment or management of MCI or mild to moderate dementia (Table 1; eTable 4 in the Supplement).…”
Section: Resultsmentioning
confidence: 99%
“…Eighty-eight RCTs (n = 14 880; mean patient age, 78 years) evaluated the effect of multiple types of caregiver or caregiver-patient dyad interventions (Table 1). Most randomized more than 100 caregivers or caregiver-patient dyads. About one-half of the studies followed up participants for 1 year or longer, and almost all focused on patients with moderate dementia.…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included RCTs are summarized in Table 1. MBIs in the included RCTs involved the following: MBSR (Brown et al, 2016;O'Donnell, 2017;Whitebird et al, 2013); MBCT (Cheung et al, 2020;Kor et al, 2019;Norouzi et al, 2014); a combination of MBSR and MBCT (Oken et al, 2010); ACT (Losada et al, 2015;Márquez-González et al, 2020); and other mindfulness-based interventions (Danucalov et al, 2013(Danucalov et al, , 2017Lavretsky et al, 2013;Leach et al, 2015;Spalding-Wilson et al, 2018;Waelde et al, 2017). MBIs were delivered as in-person, group-based sessions in all studies except for three studies, including MBIs delivered individually in person (Losada et al, 2015;Márquez-González et al, 2020) and as daily self-practice using guided audio meditations (Lavretsky et al, 2013).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%